Constituting Central American-Americans : transnational identities and the politics of dislocation - Cardenas, Maritza E. (Rutgers University Press, 2018)
"Central Americans are the third largest and fastest growing Latino population in the US. And yet, despite their demographic presence, there has been little scholarship focused on Central Americans in the US. Constituting Central American-Americans is an exploration of the historical and disciplinary conditions that have structured US Central American identity and of the ways in which this identity challenges the way we frame current discussions of Latina/o, American ethnic, and diasporic identities. In focusing on the formation of Central American identity in the U.S., and specifically within the city of Los Angeles, this book challenges us to think about Central America and its diaspora in relation to other US ethno-racial identities. By calling attention to Central America(n) as an important discursive category of analysis, Martiza Cárdenas unsettles not only scholarship that promotes the Latina/o dyad but also the binary nature of hemispheric studies that parcels the world into east/west and north/south, which in turn excludes the important role the isthmus has played in global events. In addition, studying Central America and US Central Americans further disrupts US American constructions of seeing this geopolitical space as America's "backyard" (a space outside of the confines of the US political landscape) and Central Americans as peripheral to the American body politic"-- Provided by publisher
Keywords: Central American Americans -- Ethnic identity.; Central Americans -- United States -- Social life and customs.; Hispanic Americans -- Ethnic identity.; Américains d'origine centraméricaine -- Identité ethnique.; Centraméricains -- États-Unis -- Mœurs et coutumes.; SOCIAL SCIENCE -- Discrimination & Race Relations.; SOCIAL SCIENCE -- Minority Studies.; Hispanic Americans -- Ethnic identity; United States; America.; American.; California.; Central America.; Central Americanness.; Latin America.; Latina.; Latinidad.; Latino.; Los Angeles.; diaspora.; ethnic.; identity.